PENGARUH PIJAT OKSITOSIN TERHADAP PENGELUARAN ASI PADA IBU NIFAS DI TPMB N DI KAB. BEKASI TAHUN 2021 - Khoiriah, Restu (Journal of Midwifery Tiara Bunda, 2024)
Background: Decreased milk production and milk production in the first days of delivery can be caused by a lack of prolactin and oxytocin hormone production. Research Objectives: To determine the effect of oxytocin massage on breast milk production in postpartum mothers at TPMB N di Kab. Bekasi. Research Methods: This research is a descriptive Quasi Experiment, which is a type of research design that has a control group and an experimental group not chosen randomly, and a One Group Pretest Posttest design, namely an experimental design carried out in one different groups, which aims to determine the expenditure of breast milk in postpartum mothers. about the implementation of oxytocin massage in increasing breast milk production in postpartum mothers at TPMB N di Kab. Bekasi. Result of Research: Respondents before being given oxytocin massage, the production of breast milk was not smooth as many as 19 postpartum mothers (63.3%). And it was found that all respondents before being given oxytocin massage had less than 30 postpartum mothers (100%). Conclusion: There is an effect of oxytocin massage on breast milk production in postpartum mothers at PMB Siti Suhartati, Str.Keb in 2022 with p value = 0.001 (p <0.05) Suggestion: In accordance with what has been conveyed in the study that oxytocin massage is physiological, hopefully with this research the respondents, especially for postpartum mothers, can apply knowledge about oxytocin massage